1998
DOI: 10.1007/s004380050649
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of the RAD51 and DMC1 homologs from Arabidopsis thaliana

Abstract: By using RT-PCR and degenerate oligonucleotides based on the sequence homology between the yeast RAD51 and DMC1 genes, two genes belonging to the RAD51 and DMC1 families were isolated from Arabidopsis thaliana ecotype Columbia. A RAD51 genomic DNA was also sequenced which is almost identical to its Landsberg erecta counterpart, except for a few translationally silent substitutions and for the presence of a 527-bp element downstream of the polyadenylation site. This element is repeated in the genome of Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
166
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(174 citation statements)
references
References 49 publications
(90 reference statements)
6
166
0
Order By: Relevance
“…In plants, RAD51 (Doutriaux et al, 1998;Bleuyard et al, 2006) and RAD54 (Osakabe et al, 2006;Shaked et al, 2006) homologs have been identified, leaving the question of whether plants contain RAD52 homologs (Iyer et al, 2002;Mortensen et al, 2009) or whether their absence may be compensated for by two plant BRCA2 homologs (Siaud et al, 2004;Abe et al, 2009). Nevertheless, the absence of RAD52 in plants is somewhat intriguing, considering its role in mediating critical steps of homologous recombination and its relatively high conservation across eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, RAD51 (Doutriaux et al, 1998;Bleuyard et al, 2006) and RAD54 (Osakabe et al, 2006;Shaked et al, 2006) homologs have been identified, leaving the question of whether plants contain RAD52 homologs (Iyer et al, 2002;Mortensen et al, 2009) or whether their absence may be compensated for by two plant BRCA2 homologs (Siaud et al, 2004;Abe et al, 2009). Nevertheless, the absence of RAD52 in plants is somewhat intriguing, considering its role in mediating critical steps of homologous recombination and its relatively high conservation across eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, homozygous disruption of the DMC1 gene in mouse parallels some aspect of the yeast dmc1 mutations in that it also affects meiosis, although leading to apoptosis, which was not observed in yeast (Pittman et al, 1998;Yoshida et al, 1998). In Arabidopsis, an ortholog of the yeast DMC1 gene, AtDMC1 , has been described (Sato et al, 1995;Klimyuk and Jones, 1997;Doutriaux et al, 1998). It is a single-copy gene that is expressed in young flower buds when cells are undergoing meiosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the conserved sequences and functions of rice SDS and RCK shown in this study, a small number of rice meiosis genes have been studied including PAIR2 [43], OsDMC1 [44], OsRad21-4 [45] and their functions in rice male meiosis are conserved compared to their correspondent homologous genes ASY1 [58], AtDMC1 [59,60], SYN1 [61] in Arabidopsis. In Arabidopsis, the ASY1 protein is localized to the axial/lateral elements and an asy1 mutant is asynaptic and unable to form SC in both male and female meiocytes, indicating its critical role in SC formation [54,58,62].…”
Section: Conserved Male Meiosis In Monocots and Eudicotsmentioning
confidence: 95%